Characterization of gelatin composite with low content hydroxyapatite and the influence on mesenchymal stem cell culture - Junjira T. (2017)
© 2016 Trans Tech Publications, Switzerland. In tissue engineering, hydrogel-based scaffold is one of the most common method for bone tissue engineering. Gelatin is a common material for scaffold, whereas hydroxyapatite (HA) has a similar composition and structure to natural bone mineral. HA can also increase cell adhesion ability of the scaffold. This research focuses on the fabrication of hydrogel scaffolds using gelatin composite with nanocrystalline hydroxyapatite (nHA). Then the mechanical and physical caharacteristics of the scaffold is investigetad. Low contents nHA is introduced into gelatin in order to modulate mesenchymal stem cell (MSC) behavior. There are three types of scaffolds which contain various HA content. The gelatin is crosslinked with glutaraldehyde before freeze-drying. The Young's modulus of the surface is investigated using Atomic force microscopy (AFM). The pore size is investigated using scanning electron microscope (SEM). Human MSCs are culture on the scaffold for 3 weeks. The result shows the sucesse in cell cultivation. However, the human MSCs cultured on the fabricated hydrogels do not show any lineage-specific differentiation.